Respiration rate estimation from channel state information in wireless body area networks. Issue 10 (1st May 2014) - Tsouri, G.R.; Maimon, O.
Abstract : Respiration rate is an important measure for assessing a patient's health and is typically measured using obtrusive devices. A non‐obtrusive method of estimating respiration rate by taking advantage of data packets being sent from sensor nodes in a wireless body area network is proposed and investigated. In contradistinction to other methods, the proposed method does not require dedicated hardware and does not impose overheads on transmission power and throughput. Instead, it makes use of data packets already being sent to support some other physiological monitoring applications such as cardiac, temperature or motion monitoring. The method is demonstrated on a single subject and results are presented from a study including 40 measurements taken from eight subjects. The mean estimation error in the study was 0.58 breaths per minute. The proposed method can be used to augment wireless body monitoring applications with important respiration rate measurements without imposing overheads on the compact sensor nodes.